Gender-based differences in primary percutaneous coronary intervention in patients with myocardial infarction from a developing country: A retrospective cohort study. (April 2022) - Yasmin, Farah; Kumar, Sumeet; Singh, Manjeet; Sagar,; Kumar, Karan; Parkash, Om; Asghar, Muhammad Sohaib; Jawed, Fareeha; Kirmani, Tooba Ahmed; Alam, Muhammad Tanveer
Abstract: Introduction: Limited data exists about gender's impact on differences in risk factors and outcomes in our setting. Therefore, we sought to ascertain sex-related differences in patients with AMI in our setting. Material and methods: This retrospective study analyzed data from 247 myocardial infarction patients hospitalized in a tertiary care hospital, between March and October 2020. After hospital admission, all patients underwent ECG, myocardial enzymes, troponin and other biochemical tests followed by primary PCI. Results: Patients were divided in two groups male (n = 153, mean age 55.2 ± 11.0 years) and female (n = 94, mean age 58.4 ± 12.7 years). The prevalence of smoking was higher in males than females (22.8% vs. 3.1%, p < 0.01) and so was history of three-vessel disease (3VD; 18.9% vs. 7.4%, p = 0.013). History of myocardial infarction was lower in females than males (13.8% vs. 24.8%, p = 0.03) however the age did not vary significantly between the two groups (p = 0.21). Serum creatinine (sCr) levels (1.0 ± 0.77 μmol/L vs. 1.2 ± 0.73 μmol/L, p = 0.28) and body mass index (28.4 ± 5.3 vs 27.4 ± 4.8, p = 0.45) were lower in females as compared to males, however not statistically significant. The incidence of major adverse events, severe arrhythmia and in-hospital outcomes showed no significant difference (p > 0.05) between the two groups. Post-op TIMI score and average length of hospital stay were not statistically different either (3.29 ± 2.9 vs. 2.6 ± 1.7, p = 0.726). Conclusion: Our study shows that females have a comparable age of onset of major cardiovascular events as that of males. Post-PCI clinical outcomes and in-hospital stay had no significant differences between the two groups. Highlights: What is already known on this topic: Limited data exists about gender's impact on differences in risk factors and outcomes STEMI in developing countries like Pakistan. Previous analyses on gender disparities have revealed higher mortality in females compared to males when hospitalized for STEMI. What this study adds: The incidence of major adverse events during in-hospital stay showed no significant difference among gender. The prevalence of smoking and 3VD in males was higher than in females. Despite of differences in co-morbidities between the groups, clinical outcomes remained consistent.